Privacy-preserving scheme for logistics systems based on 2D code and information hiding - Wen-bo YAN; Yuan-zhi YAO; Wei-ming ZHANG; Neng-hai YU (网络与信息安全学报)
With regard to the user privacy leakage problem in existing logistics systems,a privacy-preserving scheme for logistics systems based on 2D code and information hiding was proposed.The information hiding tech-nique was used in the proposed scheme to embed the user privacy information into the 2D code on the logistics waybill to achieve access control.To secure the user privacy information,a JPEG image stenographic algorithm for 2D code was designed.Experimental results demonstrate that this algorithm can guarantee the high undetectable performance and the stego 2D code can be correctly decoded.Using the proposed scheme,the institution or the per-son that has the access right can obtain the important privacy information so that the express can be delivered cor-rectly and the user privacy can be preserved.